Navigating Emotional Dynamics in Ai Adoption: Integrating Grief Cycle with TAM in The Context of ChatGPT Use in Indonesian Public R&D Institutions and Higher Education - Setiawan, Sigit (Universitas Muhammadiyah Surakarta, 2025)
This study integrates the Grief Cycle with the Technology Acceptance Model (TAM) to explore the emotional dynamics of adopting ChatGPT, a deep learning-based technology, at Indonesia's National Research and Innovation Agency (BRIN), with implications for enhancing personalized learning in higher education. Synthesizing data from three secondary studies, quantitative TAM analysis, qualitative topic modeling from a 2023 survey, and Grief Cycle analysis of BRIN's organizational changes (2016-2019), this research maps researchers' emotional responses, from denial to acceptance, toward AI adoption. Findings reveal that perceived usefulness drives adoption intent, but ethical concerns, such as risks of dependency and threats to scientific integrity, limit adoption rates. This framework provides novel insights into managing emotional barriers to disruptive technologies in Indonesia's public R&D context. By drawing parallels to higher education, it offers strategies to overcome faculty resistance to AI, supporting personalized learning through adaptive tools like virtual tutors. Policy recommendations, including ethics training and transparency guidelines, promote sustainable and responsible AI adoption in R&D and higher education.